2015
DOI: 10.7152/jipa.v35i0.14728
|View full text |Cite
|
Sign up to set email alerts
|

China’s Early Impact on Eastern Yunnan: Incorporation, Acculturation, and the Convergence of Evidence

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Especially for later periods, there are also a considerable number of studies on the southern expansion of the Chinese empire. While earlier studies focused on the process of BSinicization^of the locals (e.g., Fitzgerald 1972), recent research has come to see the encounter between Han and locals as a complex and long-term process of mutual influence, acceptance, rejection, and everything in between, acknowledging the agency of locals and Han immigrants alike (e.g., Allard 2015;Brindley 2015;Di Cosmo 2009;Yao 2016). These studies have shown that for a long time the adoption of Han customs by the locals remained piecemeal and eclectic, while Han control of large parts of southwest China remained tenuous at best.…”
Section: Choosing a Case Study: The Narrative Of Han Imperial Expansion Into Dianmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially for later periods, there are also a considerable number of studies on the southern expansion of the Chinese empire. While earlier studies focused on the process of BSinicization^of the locals (e.g., Fitzgerald 1972), recent research has come to see the encounter between Han and locals as a complex and long-term process of mutual influence, acceptance, rejection, and everything in between, acknowledging the agency of locals and Han immigrants alike (e.g., Allard 2015;Brindley 2015;Di Cosmo 2009;Yao 2016). These studies have shown that for a long time the adoption of Han customs by the locals remained piecemeal and eclectic, while Han control of large parts of southwest China remained tenuous at best.…”
Section: Choosing a Case Study: The Narrative Of Han Imperial Expansion Into Dianmentioning
confidence: 99%
“…From the third century BC onwards, some large graves began to contain a small number Han items, e.g., crossbows, iron and composite swords, iron and bronze vessels, sometimes mirrors and banliang coins (Yang et al 2009(Yang et al , 2010. As Allard (2015) has shown, in pre-conquest times, the other hand, furnished as many as 119 Han-style objects in 10 burials, but they made up less than 1% of the assemblages (Yunnansheng et al 2007). For the former group, the Han items seem to have been of much greater importance, either as symbols of outside connections or as useful items that had been integrated into local daily life.…”
Section: Dian Archeology: Local Developments and Evidence For Central Plains Connectionsmentioning
confidence: 99%
“…We would also critically interrogate our source fields -indigenous texts or outsider reports -rather than using them uncritically as our starting point. Allard's (2015) study demonstrates why such source-side interrogation is essential to good scholarship. We would also tread carefully when applying ethnographically derived models.…”
Section: Studying the Pastmentioning
confidence: 94%
“…Archaeological research on the southern Han periphery by Francis Allard (2015), Nam , and Alice Yao (2015) offers insights to global studies of culture contact/entanglement; so does work in eastern Indonesia by Peter Lape (2000aLape ( , 2000b. Research on the post-1000 CE period, and particularly on the premodern to Early Modern transition, would fill gaps historians have found in explaining 15 th -17 th century transformations in the region.…”
Section: Studying the Pastmentioning
confidence: 99%